Oxford Primary Mathematics Workbook 3 Supplementary Reading Material - Dr Foong Pui Yee; Wong Oon Hua (Karachi: Oxforf University Press, 2019)
Chapter Opener to arouse pupils curiosity of the contents of the chapter, familiar events or occurrences that serve as an introduction for pupils Recap allows pupils to revisit learnt concepts so that they can build upon prior knowledge In Focus for pupils to discuss questions related to various lesson objectives as an introductory activity for pupils Let s Learn introduces new concepts through the Concrete-Pictorial-Abstract approach with the use of engaging pictures and manipulatives. Guided examples are also provided for reinforcement Activity Time (We Work Together, Play A Game!, IT s Fun) to allow pupils to develop requisite skills, knowledge and attitudes with the inclusion of learning experiences. It provides pupils with opportunities to work as an individual or in small groups to explore mathematical concepts and play games Practice comprises of questions for further consolidation and for immediate evaluation of pupils learning Mind Workout to encourage pupils to apply learnt concepts to solve challenging non-routine questions and to develop higher order thinking skills Maths Journal provides pupils with opportunities to show their understanding of the mathematical concepts learnt and to reflect on their learning process Self Check for pupils to assess their own learning after each chapter Add to Wish List readerhip Readership / Level For Class 3 weight Weight in kg 0.64 rights Rights For sale in Pakistan and Pakistani Schools in the Middle East only binding Binding Paperback Reviews Customers loved these too logo.png Oxford University Press advances knowledge and learning. We are a department of the University of Oxford and share the objective of excellence in research, scholarship, and education by publishing worldwide. Publish with Us Customer Services Information & Services Important links Copyright © Oxford University Press, 2025 | All Rights Reserved.
Keywords: Mathematics - Workbook; Oxford Mathematics Workbook